2017
DOI: 10.3823/2355
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and cardiorespiratory newborn adaptations during hot tub bath

Abstract: Objective: To evaluate thermal and cardiorespiratory adaptation during hot tub bath and shower in healthy newborns in the first hours of life. Study design: This is a randomized blind controlled trial, registered in ReBEC (No. RBR-4z26f3) with 184 newborns divided into hot tub group (n=84) and shower (n=100). Newborns from intervention group were immersed in a hot tub with warm water up to the neck, without exposure to air flow, and control group received traditional shower. Heart rate, respiratory rate and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
1
2
0
8
Order By: Relevance
“…In the study, it was determined that the swaddle bathing affects RR, HR, and SpO2 levels positively. This is supported by similar studies in the literature (Da Fonseca Filho et al., ). In addition, stress and pain lead to increased HR and RR in premature infants and decreased SpO2 (Als, ; Peng et al., ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the study, it was determined that the swaddle bathing affects RR, HR, and SpO2 levels positively. This is supported by similar studies in the literature (Da Fonseca Filho et al., ). In addition, stress and pain lead to increased HR and RR in premature infants and decreased SpO2 (Als, ; Peng et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…In swaddle bathing, the infant is covered with warm water during bathing, thus reducing heat changes and ensuring heat protection (Hall, ). It has been reported that the heat loss in swaddle bathing is less than conventional bathing (Da Fonseca Filho et al., ; Edraki, Paran, Montaseri, Nejad, & Montaseri, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte bebek banyosu yenidoğanda ağrı kontrolünde kullanılan nonfarmakolojik yöntemleri arasında yer almaktadır. Yenidoğanın uygun sıcaklıktaki (37-38 o C) suya batırılması (küvette banyo) ile birlikte bebekte kan dolaşımı artmakta, kaslar rahatlamakta ve sinir uçlarının duyarlılığı azalmaktadır (17) .…”
Section: Olumlu Etkilerunclassified
“…Term bebeklerde yapılan çalışmalarda da bebek banyosunun fizyolojik değerler üzerinde etkisi olduğu belirlenmiştir (5,17,29) . Ar ve Gözen küvette banyonun duş şeklinde banyo yöntemine göre oksijen satürasyonu ve KAH üzerinde daha olumlu etkileri olduğu saptamışlardır (29) .…”
Section: Fizyolojik Değerlerde Bozulmaunclassified
“…A ofuroterapia, também conhecida como "banho de ofurô", consiste em uma modalidade da hidroterapia, sendo esta utilizada como uma conduta de humanização da assistência a RNPT's estáveis clinicamente. Através da imersão corporal, do posicionamento e das propriedades da água, a aplicação da ofuroterapia em RNPT's provocará sensações semelhantes à do espaço intrauterino, como segurança e relaxamento, além de favorecer a estes um adequado desenvolvimento neuropsicomotor e afetivo 7,[12][13][14][15][16] .…”
Section: Introductionunclassified